Evidence of the formation of noctilucent clouds due to propagation of an isolated gravity wave caused by a tropospheric occluded front. Issue 6 (25th March 2015) - Dalin, P.; Pogoreltsev, A.; Pertsev, N.; Perminov, V.; Shevchuk, N.; Dubietis, A.; Zalcik, M.; Kulikov, S.; Zadorozhny, A.; Kudabayeva, D.; Solodovnik, A.; Salakhutdinov, G.; et al.
Abstract We consider a unique case of a propagating internal gravity wave that has generated in situ a compact and thin layer of noctilucent clouds (NLC) at 82.7–85.2 km with a characteristic horizontal scale of 65–70 km, as observed in the Moscow region on the night of 18–19 July 2013. This particular transient isolated gravity wave together with the whole NLC layer suddenly appeared in the clear twilight sky and lasted about 1 h traveling eastward, which differs significantly from previously observed cases of gravity waves propagating through preexisting NLC layers. Our model studies demonstrate that the wave had a tropospheric source connected to the passage of an occluded front. The wave was likely generated due to strong horizontal wind shears at about 5 km altitude.